Exploring anthocyanins, antioxidant capacity and α-glucosidase inhibition in bran and flour extracts of selected sorghum genotypes. (June 2021) - Kumari, Palety Kiran; Umakanth, A.V.; Narsaiah, T. Bala; Uma, Addepally
Abstract: Sorghum is an imperative source of health-promoting properties owing to abundant levels of polyphenols. Especially sorghum bran in some selected varieties has a higher concentration of phenolic compounds and greater antioxidant properties, showing potential food and industrial applications. In this study, bran and flour of six sorghum varieties with different pericarp color were investigated for anthocyanins, antioxidants, total phenols, flavonoids, tannins, and α-glucosidase inhibitory activities. Sorghum samples were subjected to maceration and soxhlet extractions by 1% acidified methanol. The bran and flour extracts were further analyzed using spectroscopy, High Pressure Liquid Chromatography (HPLC), and Liquid Chromatography Mass Spectrometry (LCMS). The results showed that anthocyanin content with substantial variance (p ≤ 0.05) in bran extracts was 3–4 times higher than that of flour by both extraction processes. Red-brown variety IS686 bran showed highest total polyphenols, flavonoids, tannins, and high antioxidant activity by DPPH, ABTS, and FRAP along with higher amounts of monomeric and total anthocyanins content. However, bran extract of yellow variety IS10972 showed effective α-glucosidase inhibition. Significant variation (p ≤ 0.05) among 3-deoxyanthocyanidins, flavones, and flavanones were observed from HPLC analysis. Higher amounts of 3-deoxyanthocyanidins and flavones were observed in IS686 bran whereas higher flavanones in IS10972 bran. Furthermore, major ions of apigeninidin, luteolinidin, and their derivatives were detected through LCMS analysis of IS686 bran. Hence these results are encouraging for selecting specialty sorghum bran with dietary rich components to cater for various health-improving aspects, and for further commercial exploitation in food industries. Graphical abstract: Image 1 Highlights: Sorghum bran was found to be rich source of anthocyanins, antioxidant capacity and α-glucosidase inhibition. Soxhlet and maceration influenced the extraction of phenolic compounds. Anthocyanins were identified and quantified by HPLC and LCMS. Red-brown variety IS686 bran had highest total phenolics, 3-Deoxyanthocyanidins and antioxidant capacity. High α-glucosidase inhibition activity was shown by yellow variety IS10972 bran extracts.